Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

High-precision determination of silicon nanocrystals: optical spectroscopy versus electron microscopy - Köthemann, Ronja; Weber, Nils; Lindner, Jörg K N; Meier, Cedrik (Semiconductor Science and Technology)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Structural, electronic and phononic properties of PtSe2: from monolayer to bulk - Kandemir, A; Akbali, B; Kahraman, Z; Badalov, S V; Ozcan, M; Iyikanat, F; Sahin, H (Semiconductor Science and Technology)

Interlayer charge transfer in n-modulation doped Al1−x Ga x As–GaAs single heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Influence of recombination center interaction on the photoluminescence of AlGaAs/GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

On the annealing mechanism of AuGe/Ni/Au ohmic contacts to a two-dimensional electron gas in GaAs/AlxGa1−xAs heterostructures - Koop, E J; Iqbal, M J; Limbach, F; Boute, M; van Wees, B J; Reuter, Dirk; Wieck, A D; Kooi, B J; van der Wal, C H (Semiconductor Science and Technology)

In situ characterization of ZnTe epilayer irradiation via time-resolved and power-density-dependent Raman spectroscopy - Wiedemeier, V; Berth, Gerhard; Zrenner, Artur; Larramendi, E M; Woggon, U; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Laser irradiation damage in ZnTe epilayers was analyzed in situ by power-density-dependent and time-resolved micro-Raman spectroscopy. Damage by ablation or compound decomposition on the sample surface was revealed by the decrease of the ZnTe–nLO mode intensity with the increase of laser power density. The appearance of the peaks associated with the stronger crystalline-tellurium modes, tellurium aggregates and second-order Raman scattering at room temperature μ-Raman spectra was observed for higher power densities than 4.4 × 105 W cm−2. The Raman signal time transients of ZnTe–nLO and crystalline-tellurium modes reveal an exponential evolution of the laser irradiation damage and a fast formation of crystalline tellurium aggregates on the layer surface.

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Intensity enhancement of Te Raman modes by laser damage in ZnTe epilayers - Larramendi, E M; Berth, Gerhard; Wiedemeier, V; Hüsch, K-P; Zrenner, Artur; Woggon, U; Tschumak, E; Lischka, K; Schikora, D (Semiconductor Science and Technology)
Damage caused by laser irradiation on the surface of ZnTe epilayers was studied by micro-Raman and atomic force microscopy (AFM). ZnTe LO-phonon overtones up to four order and TO + (n − 1)LO zone-center phonons were observed in the resonant micro-Raman spectra at room temperature. Discrepancies in the literature regarding the origin of two features observed at low frequencies around 120 and 140 cm−1 in the Raman spectrum of ZnTe are discussed and resolved. These Raman peaks were not detected by using a low excitation laser power density on a Zn-terminated ZnTe surface; however, with the increase of the laser power density they were found to arise irreversibly. The correspondence of these peaks in a wave number with the strongest Raman peaks of the crystalline tellurium phase and the intensity enhancement behavior with the laser power in a similar way as for CdTe strongly suggests the formation of crystalline tellurium aggregates on the layer surface due to laser irradiation damage. AFM data reveal the occurrence of laser ablation on the ZnTe surface even though the surface temperature of the sample is below the melting point.

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Preparation of electron waveguide devices on GaAs/AlGaAs using negative-tone resist calixarene - Knop, M; Richter, M; Maßmann, R; Wieser, U; Kunze, U; Reuter, Dirk; Riedesel, C; Wieck, A D (Semiconductor Science and Technology)

Dual-gate GaAs/AlGaAs quantum point contact with tuneable subband energy separation - Kähler, D; Knop, M; Kunze, U; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Layer-compensated selectively doped AlxGa1-xAs/GaAs heterostructures as a base material for nanolithography - Reuter, Dirk; Kähler, D; Kunze, U; Wieck, A D (Semiconductor Science and Technology)

Layer-compensated selectively doped AlxGa1-xAs/GaAs heterostructures as a base material for nanolithography - Reuter, Dirk; Kähler, D; Kunze, U; Wieck, A D (Semiconductor Science and Technology)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)